Developing A Textbook of Alternating Current Circuit Completed by Solving Problems Using Pythagoras Theorem - Shinta Nuriyah Mahbubiyah Royani; Bambang Supriadi; Maryani Maryani (Jurnal Ilmiah Pendidikan Fisika, 2023)
One of the most difficult chapters in physics is alternating current circuits. This material is also one of the materials tested in the university test. This is because the material requires a fairly complicated mathematical approach. Additionally, the alternating current circuit textbooks that have been used so far still use too high language. Therefore, the researchers need a simple way that can facilitate students in solving alternating current circuit problems and be packaged in a textbook. A simple way to solve alternating current problems can be done using the Pythagorean theorem. This is because the two are identical. Therefore, the purpose of this research is to develop a textbook on alternating current circuit material accompanied by a solution using a simpler method, namely the Pythagorean theorem. This study uses a research and development model with the ADDIE (Analysis, Design, Development, Implementation, and Evaluation) stages. There were five research instruments used: (1) validation sheets; (2) teacher interview sheets; (3) teacher and student needs sheets; (4) test sheets; and (5) student response questionnaire sheets. The developed textbook has been validated by two experts and one user with a percentage value of 89.13%, so it is in the very valid category. In addition, based on the results of field tests on 34 class XII students of Senior High School in Jember, it is known that the developed textbook obtained an effectiveness percentage of 83.46% with an N-Gain value of 83.46. The textbook is in the high category and has a response questionnaire percentage of 80.3, so the developed textbook received a very positive response from students. By using this textbook, students can solve alternating current circuit problems more effectively and efficiently.